2023
DOI: 10.3390/polym15092038
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Allyltrimethylisilane and 4-Methyl-1-Pentene by Using Metallocene Catalysts

Abstract: Polymers of higher olefin, obtained by Ziegler-type polymerization, have been used in some critical fields, e.g., as the membrane for extracorporeal membrane oxygenation (ECMO), which plays an important role in the treatment of patients with severe COVID-19. The polymer obtained by a single-site catalyst, e.g., metallocene catalysts, demonstrated a higher performance. The homo- and co-polymerization of allyltrimethylisilane (ATMS) and 4-methyl-1-pentene (4M1P) were conducted using syndiospecific (cat 1) and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Finally, the copolymerization of 4MP with functional monomers was also started to be investigated. In particular, Wang et al 41 reported the synthesis of 4-methyl-1-pentene/ allyltrimethylisilane copolymers in a wide composition range prepared with isospecific and a syndiospecific metallocene catalysts. They obtained crystalline materials with high melting temperatures but characterized by rather low molecular weights.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Finally, the copolymerization of 4MP with functional monomers was also started to be investigated. In particular, Wang et al 41 reported the synthesis of 4-methyl-1-pentene/ allyltrimethylisilane copolymers in a wide composition range prepared with isospecific and a syndiospecific metallocene catalysts. They obtained crystalline materials with high melting temperatures but characterized by rather low molecular weights.…”
Section: ■ Introductionmentioning
confidence: 99%